PECULIARITIES OF IMMUNE RESPONSE TO TUBERCULIN IN CHILDREN WITH HIGH SENSITIVITY TO IT - T.Ya. Tyul'kova; A.S. Kornachev; Yu.P. Chugayev; E.A. Kashuba; N.V. Kozlov; E.F. Khemeleva ("Paediatrician" Publishers LLC, 2010)
According to normative documents regulating anti-tuberculosis measures, children with hyperergy to tuberculin (papule _ 17 mm) are in risk group of development of local tuberculosis. Patients with hyperergy to tuberculin are treated with two anti-tuberculosis drugs for minimization of this risk. Children and adolescents with high sensitivity to tuberculin (papule = 15-16 mm) can be treated with one drug. Present study proved that selection of patients into corresponding risk groups based on subjective measures of papule diameter lead to low effectiveness of preventive treatment in children with high sensitivity to tuberculin. An analysis showed that patients with high sensitivity and hyperergy to tuberculin have comparable frequency of different social, epidemiological, clinical and immunopathological states and rates of immunological tests. This fact shows necessity of observation of children with papule 15-16 mm as a reaction for 2 tuberculin units in frames of VI B group and performance of preventive treatment with two antituberculosis drugs. Key words: children, tuberculin, sensitivity, hyperergy, immune system. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(4):22-26)